A Bibliometric Analysis of Drinking Water Distribution In Coastal Areas Using Vosviewer - Aluna Ricardo, Vincent; Irfan Rifai, Andri; Savitri, Amanatullah Savitri; Prasetijo, Joewono (Asian Journal of Social and Humanities, 2024)
This research aims to determine the trend related to drinking water distribution in coastal areas using VOSViewer software  Bibliometric analysis is a statistical method that could quantitatively analyze a research paper focusing on one topic mathematically. This research was analyzed using bibliometric analysis focusing on drinking water distribution in coastal areas. This research uses the bibliometric analysis method to examine a keyword. This method is often used to explore and analyze much scientific data. The Crossref database was used to retrieve approximately 1000 research with interrelated topics. Retrieved data is helped by using Publish or Perish and saving in RIS (Research Information System) extension. VOSViewer is also used to help process data into visualization. Drinking Water Distribution System has become the most dense keyword shown by VOSViewer. The publication is mostly in journal articles, totaling 549 out of 1000. Research on drinking water distribution systems in coastal area-related topics is continuously increasing by number year by year. With time stamps between 2000-2023, the highest peak was in 2023, with 75 publications in a year.